ESP in Business Communication: Implications for Vocational Education in Indonesia - Wijayati, Titik; Safitri, Yulita Dwi (International Journal of Research in Vocational Studies (IJRVOCAS), 2025)
This paper examines the role and implementation of English for Specific Purposes (ESP) in business communication within the context of Indonesian vocational education. As Indonesia integrates into the global economy and the ASEAN Economic Community, there is a growing demand for vocational graduates who possess industry-specific language competence alongside technical skills. The study synthesizes literature and current practices to highlight the shift from General English to Business English, which aims to equip students with practical skills for workplace interactions such as correspondence, presentations, and negotiations. However, the review identifies significant challenges hindering effective implementation, including insufficient teacher training in ESP methodologies, a lack of authentic and localized teaching materials, and varying levels of motivation and proficiency. Furthermore, misalignments between national curriculum standards and specific industry need often to constrain innovation in the classroom. The paper concludes by outlining key implications for improvement, recommending the adoption of rigorous needs analysis, specialized professional development for teachers, and stronger collaboration between vocational institutions and industry partners to develop relevant curricula and resources. These strategies are essential for ensuring that vocational education in Indonesia produces graduates who are competitive in the modern workforce.